1996
DOI: 10.2323/jgam.42.235
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic comparison of enzymes as a chemotaxonomic aid among Aspergillus taxa: (3) The identity of the xerophilic species A. penicillioides in subgenus Aspergillus section Restricti.

Abstract: The identity of the xerophilic species Aspergillus penicillioides and related taxa has been studied chemotaxonomically using polyacrylamide slab gel electrophoresis. In a dendrogram based on the calculated similarity values of five enzymes, 14 isolates of A. penicillioides in subgenus Aspergillus section Restricti and 28 isolates of related taxa in subgenus Aspergillus formed 22 clusters at a 60% similarity level. A. penicillioides isolates were scattered over the 11 clusters. In the ubiquinone systems, all is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Clavati. Based on the results of this study and former studies (Tamura et al, 1996(Tamura et al, , 1999, we concluded that species of Aspergillus showing DNA relatedness at 70% or greater are conspecific, as was shown for the yeasts (Kurtzman, 1987).…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…Clavati. Based on the results of this study and former studies (Tamura et al, 1996(Tamura et al, , 1999, we concluded that species of Aspergillus showing DNA relatedness at 70% or greater are conspecific, as was shown for the yeasts (Kurtzman, 1987).…”
Section: Resultsmentioning
confidence: 92%
“…At a 60% similarity level, which was adopted by the numerical analysis of enzyme patterns and DNA-DNA hybridization of Aspergillus spp. reported by Tamura et al (1996) and Yamatoya et al (1990), the 15 strains were separated into 9 major clusters. Each cluster corresponds to nine named taxa of Aspergillus: cluster 1 to A. restrictus (xerophilic), cluster 2 to Eurotium chevalieri (xerophilic), cluster 3 to 6 strains of A. clavatus, cluster 4 to A. clavatonanicus, cluster 5 to 2 strains of A. giganteus, cluster 6 to A. brunneo-uniseriatus in sect.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A. penicillioides strains were scattered over 11 clusters and exhibited their great divergence. Among A. penicillioides strains, IFO 8155 (originally described as A. vitricolae [sic]) did not group with A. penicillioides NRRL 4548 (ex neotype), but were placed in the cluster 15 with three strains of A. penicillioides (cf., Tamura et al, 1996). They concluded that A. penicillioides strains, all having Q-9 as the major ubiquinone system, are genealogically diverse and presumably represent several species.…”
mentioning
confidence: 99%